The ins and outs of the Mycobacterium tuberculosis-containing vacuole - Russell, David G. (Cell Microbiol, 2016)
The past few years have seen publication of reports from several groups documenting the escape of Mycobacterium tuberculosis (Mtb) from its intracellular vacuole to access the cytosol. The major questions addressed in these publications are the mechanism(s) underlying this process, the frequency of its occurrence, and most importantly, the biological significance of this phenomenon to bacterial survival, growth and virulence. I believe that the first two questions are moving towards resolution but questions relating to biological context have yet to be answered fully. In this viewpoint article I will try to convince the readers why escape from the vacuole in no way diminishes the significance of Mtb’s intravacuolar survival mechanisms, and why, as a lab, we continue to focus the majority of our efforts on the “bug in the bag”.